#TITLE_ALTERNATIVE# - Andrian Yusuf , Wendi
The Nautilus species is a deep-sea animal that existed about 500 million years ago. Nautilus is a cephalopoda class that has a beauty in its shell. Tourists, visiting the tropics for underwater trips, can see Nautilus directly, and the Nautilus fossil itself is found in various archaeological sites and museums spread all over the world. Nautilus's dead shells are common to be home to other marine animals such as fish and shrimp, or drifted by the ocean currents to the edge of the beach and taken by passing coastal people. Nautilus species that have not changed much in the shape of their body and dubbed as one of the fossil hidup.Penduduk around the location of the population Nautilus began chasing shells because of the large market demand and only found in the Atlantic sea around the archipelago of Indonesia, the Philippines, the Atlantic Islands, and the north continent of Australia. Researchers conducted expeditions and research and found the fact that the population of Nautilus was drastically reduced in the last century. The hunting law is issued for rare animals to be protected but wild hunting continues, even in the southeast asia rich in biodiversity. Wild poaching continues to occur as market demand by foreign tourists encourages residents to seek income through the sale of nautilus shells. Increased public awareness of the threat of extinction of nautilus in the area of tourist attraction frequented by foreign tourists. Place lodging such as hotels, is one of the foreign tourist destinations. The hotel lobby is a strategic location for placing ceramic wall hangings as a means of raising awareness of Nautilus extinction.